2021
DOI: 10.31289/diversita.v7i2.4540
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Beban Kerja Dan Stres Ibu Yang Bekerja Pada Masa Pandemi Covid- 19

Abstract: Penelitian ini bertujuan untuk meneliti lebih dalam tentang bagaimana beban kerja dan stress ibu yang bekerja dimasa pandemi di lhokseumawe dan aceh utara. Pendekatan penelitian ini menggunakan penelitian kualitatif dengan tipe penelitian diskriptif. Pemilihan subjek penelitian ini menggunakan teknik purpose sampling sebanyak 4 orang yaitu ibu- ibu yang bekerja di lhokseumawe dan aceh utara. Metode Pengumpulan data yang digunakan dalam penelitian ini dengan megunakan metode observasi langsung terlibat pasif, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…These factors can have detrimental effects on the body's immune system, as highlighted by Safarina et al in 2021.This finding aligns with the research conducted by Khaerunnisa et al, in 2022, which suggests that women have a higher susceptibility to stress when confronted with novel situations. [8][9][10] Pharmaceuticals Remdesivir and Favipiravir are antiviral agents that have demonstrated efficacy in individuals with moderate to severe symptoms. These medications belong to the class of prodrug nucleotide analogues and are capable of inhibiting the RNA polymerase of the COVID-19 virus.…”
Section: Sexmentioning
confidence: 99%
“…These factors can have detrimental effects on the body's immune system, as highlighted by Safarina et al in 2021.This finding aligns with the research conducted by Khaerunnisa et al, in 2022, which suggests that women have a higher susceptibility to stress when confronted with novel situations. [8][9][10] Pharmaceuticals Remdesivir and Favipiravir are antiviral agents that have demonstrated efficacy in individuals with moderate to severe symptoms. These medications belong to the class of prodrug nucleotide analogues and are capable of inhibiting the RNA polymerase of the COVID-19 virus.…”
Section: Sexmentioning
confidence: 99%
“…According to research by Safarina, Amalia, and Dewi (2021), mothers experience stress due to the COVID-19 pandemic situation, especially activities related to online schools and health risks when working outside the home. Susilowati and Azzasyofia (2020) found that 71.88 percent of mothers experienced high s of stress.…”
Section: Introductionmentioning
confidence: 99%